Transforming happiness management in Spanish SMEs: the role of consultants - Núñez-Sánchez, José Manuel; Ahumada-Tello, Eduardo; Gálvez-Ruíz, Pablo; Molina-Gómez, Jesús (Springer Nature, 2025)
This research project was born out of a consultancy endeavor, responding to the emerging trend in the Spanish market towards adopting well-being and happiness initiatives within companies. Its primary aim is to develop a formal framework for a happiness management certification explicitly tailored for Spanish SMEs, with the indispensable assistance of external consultants. A mixed-methods approach combining quantitative and qualitative techniques has been employed to achieve this objective, ensuring a comprehensive and multifaceted analysis. The study unfolds through sequential phases, commencing with an exhaustive review of existing literature, followed by a quantitative assessment to gauge the happiness levels among the workforce nationwide. Additionally, semi-structured, in-depth interviews with experienced practitioners were conducted to refine the proposed framework, emphasizing the significance of corporate social responsibility and the promotion of internal and external happiness. The outcome of this endeavor is a structured consulting framework designed to facilitate the attainment of a Happiness Management Certificate within SMEs. This underscores the pivotal role of management consulting in fostering the dissemination of valuable and groundbreaking insights for SMEs to foster employee well-being with its myriad benefits and reinforce their competitive advantage. Moreover, it addresses the gap between large corporations and SMEs in accessing certified happiness management, obviating the need for cumbersome and expensive infrastructures through the guidance of adept consultants.
Transformando la gestión de la felicidad en las pymes españolas: el papel de los consultores
Keywords: Felicidad - Gestión; Happiness Management; Well-being; Certification; Human Resources; Consulting; SMEs